2015
DOI: 10.1016/j.jff.2015.01.045
|View full text |Cite
|
Sign up to set email alerts
|

The oral bioavailability of curcuminoids in healthy humans is markedly enhanced by micellar solubilisation but not further improved by simultaneous ingestion of sesamin, ferulic acid, naringenin and xanthohumol

Abstract: Available online A B S T R A C TCurcuminoids (curcumin, demethoxycurcumin and bis-demethoxycurcumin) are poorly absorbed and rapidly metabolised and excreted. We investigated in healthy young and aged women and men if co-administration of adjuvants (sesamin, ferulic acid, naringenin, and xanthohumol) alone or in combination with micellar solubilisation improves the bioavailability of curcuminoids. A single oral dose of 98 mg curcuminoids was administered as native curcuminoids (NC), native curcuminoids plus ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 36 publications
9
67
2
Order By: Relevance
“…The administration of solid lipid curcumin particle formulations in osteosarcoma patients at doses of 4 g/ day resulted in maximum curcumin plasma concentrations of 41 ng/ml (28), which is fivefold lower than those reported here. The micellar curcumin formulation used in the present study, which was already shown to have superior oral bioavailability in humans over other formulations (18,19), should therefore be the formulation of choice for future studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The administration of solid lipid curcumin particle formulations in osteosarcoma patients at doses of 4 g/ day resulted in maximum curcumin plasma concentrations of 41 ng/ml (28), which is fivefold lower than those reported here. The micellar curcumin formulation used in the present study, which was already shown to have superior oral bioavailability in humans over other formulations (18,19), should therefore be the formulation of choice for future studies.…”
Section: Discussionmentioning
confidence: 95%
“…To overcome this pharmacokinetic deficit, a number of strategies have been employed to increase the water solubility, physical stability, and intestinal permeability of curcumin. These strategies include ingestion in combination with other foods, formulation as micronized powders, combination with additional phytochemicals, and the development of controlled-release and nano-formulations (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Native curcuminoids have poor oral bioavailability , which may explain why previous human studies testing native curcuminoids have led to variable results. We hypothesize that curcuminoids with improved bioavailability will lower plasma lipids and inflammation in subjects at risk for the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of curcuminoids levels in plasma after administration of fresh turmeric juice powder was carried out by a standardized HPLC-DAD-ESI-MS/ MS procedure and the pharmacokinetic parameters were deducted from the plasma curcumin concentration-time plot as reported earlier (Cuomo et al, 2011;Krishnakumar et al, 2012). The relative absorption of curcumin from FTC in comparison with the standard curcumin DTC, was expressed in terms of the area under curve (AUC), since it is regarded as the most reliable method of expressing the absorption unlike the maximum plasma concentration of the drug (Cmax) which is just a single time point measurement (Kocher, Schiborr, Behnam, & Frank, 2015). Range and linearity for curcumin extracted from plasma was confirmed by spiking the standard curcumin and the internal standard, salbutamol.…”
Section: Plasma Curcuminoids Absorption Measurementsmentioning
confidence: 99%